Examining collocations in EFL Textbooks and Providing Teaching Guidelines (British Journal of Multidisciplinary and Advanced Studies, 2023)
The aim of this study is to analyze the four most common collocation types found in seventh- through ninth-grade English textbooks (verb-noun, adjective-noun, verb-preposition, and adjective-preposition), with a primary focus on the reading texts. The research aimed to develop pedagogical guidelines relevant to the communicative paradigm and eclecticism, as a result. This study used a descriptive-analytical research design, specifically a content analysis method, to identify the accented collocations throughout a set of junior high school English textbooks. It was discovered that only 9% collocations out of the vocabulary found in the textbooks is present in the three books, while only 1% is found in Band II of the Revised English Curriculum of the Ministry of Education (2013), which includes all possible collocations for intermediate level learners (from the seventh to the ninth grades). Implications for the classroom were drawn from the research.